Digital transformation strategies for small, medium, and large companies. driving the digital transformation based on Netguru-s expertise - Salgarolo, Julia (2022)
The topic of digital transformation strategies is the focus of this paper. The organization chosen for the study is Netugru -a Polish software and development company, and its experts who work with digital transformation and strategy development consist of the research sample. The empirical part aims at exploring what are the digital transformation strategies for small, medium, and large companies. The findings show, among others, the main objectives for digital transformation as well as the elements and aspects important to consider for organizations of various sizes. Thus, the differences and similarities in digital transformation strategy have been explored.